Exploring students' perceptions of bullying: a case study in a Malaysian higher education institution / Nik Sarina Nik Md Salleh ... [et al.] - Nik Md Salleh, Nik Sarina; Khairil Annuar, Nurhuda; Mohd Razli, Atirah; Shaharuddin, Syahirah; Ab Malik, Mohamad Hidayah; Ibrahim, Mohd Amiruddin; Tun Ismail, Wan Nor Azilawanie; Tanjung, Hasrudy; Jusoh, Mohd Sallehin (Universiti Teknologi MARA, Perlis, 2024)
Recognized as a significant source of trauma for adolescents, bullying necessitates an ecological framework to achieve a comprehensive understanding. Thus, this study pursued three main objectives: evaluating students' perceptions of bullying in a higher learning institution, analyzing influencing factors, and comparing perceptions between male and female students. To gather the required data, questionnaires were administered to a sample of students from an institution. Out of a total student population of 6190, 361 questionnaires were distributed, resulting in a 41% response rate. The results indicated a high perception of bullying occurrence. Peer pressure emerged as the most influential factor, obtaining the highest agreement with an average rating of 4.41, emphasizing its significance. The family factor ranked second at 4.07, while the individual factor received the lowest mean rating at 3.91. Meanwhile, no significant gender impact was observed. A key recommendation for future research is for students to proactively address bullying by reporting incidents, asserting their rights, and avoiding silence to prevent potential mental and physical health issues. Cultivating friendships is crucial, and parents should focus on bonding with their children to deter bullying. Boosting self-esteem is another vital measure to reduce the likelihood of becoming a target for bullies. Given the absence of gender-based distinctions in bullying, higher educational institutions should actively promote awareness about bullying for all students, regardless of gender.